Cyclic Sulfamide HIV-1 Protease Inhibitors : Design, Synthesis and Modelling - Ax, Anna (Uppsala universitet, Institutionen för läkemedelskemi, 2005)
Ten years ago, the first protease inhibitor targeting the human immunodeficiency virus (HIV) was approved for clinical use. Highly active antiretroviral therapy (HAART), which combined protease and reverse transcriptase inhibitors, quickly became the standard therapy for treating patients infected with HIV and Acquired Immune Deficiency Syndrome (AIDS). Nevertheless, last year the AIDS pandemic reached its highest level ever. Many infected patients, mainly in the developing countries, are still without treatment. Among those patients who receive treatment, an increase in drug resistance and new-infection with drug-resistant strains are seen. To come to terms with these problems, new drugs that are efficient against resistant strains and can be produced at low cost are needed. In this study, we have focused our research efforts on cyclic sulfamides active as HIV-1 protease inhibitors. Distinctive to this compound class, as compared to the inhibitors so far approved for clinical use, was the incorporation of a water mimic that displaces the structural water (W301) observed in the X-ray crystal co-complexes. The first part of the study was aimed at understanding the rationale behind the nonsymmetric binding mode that the inhibitor adopted when bound to the enzyme. Symmetric and nonsymmetric inhibitors were synthesized and the structure-activity relationships and preferable binding modes were rationalized with the help of Comparative Molecular Field Analysis (CoMFA). In the second part of the study, an attempt was made to reduce the size of these inhibitors. As a result, the traditional P1/P1' substituents were removed, while the P2/P2' substituents were elongated in an attempt to reach between the binding sites. The design hypothesis was shown to be successful and inhibitors possessing nanomolar activity were identified.